Seasonal variations in the physico-chemical characteristics of water from various tourist spots of Kanyakumari District (International Journal of Food and Nutritional Sciences, 2022)
The present study was carried out to determine the Physico-chemical characteristics of water from selected tourist spots of Kanyakumari district during the period of twelve months from June 2016 to May 2017. Five sampling stations were selected and water samples were collected for the study. Surface water temperature varies from 24.2 to 31.5oC, atmospheric temperature varies from 25 0C to 32.5 0C, pH was ranged between 6.23 to 8.12. Variation of Dissolved Oxygen content was 4.2 to 6.7 mg/l. The ranges of chloride from 10 to 21100 mg/l. TDS value ranges from 30 to 41234 mg/l. The ranges of nitrate, nitrite and phosphate were 0.5 to 4 mg/l, 0.03 to 0.43 mg/l and 0.1 to 1.05 mg/l respectively. Electrical conductivity ranges from 45 to 62114 µs/cm. Total hardness ranges from 12 to 17300 mg/l.